Design and Implementation of a Career Guidance Portal Embedded With Digital Library and Skill Assessment Tool - Kritika Vishwakarma; Peeyush Kumar Pathak (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This project presents a Vision To Human Society website designed to help users explore potential career possibilities and make thoughtful life decisions. The site features an easy-to-navigate, user-friendly interface where people can look at their interests, skills, and values using interactive tools and personalized assessments. Using up-to-date web technology, the website provides meaningful recommendations and pathways generated according to each users' unique profile. The website is fully responsive and accessible, and seeks to provide individuals at various points in their lives practical guidance to help them navigate their career journeys and personal growth.
Keywords: Career Guidance; Life Path Analysis; Machine learning in career analysis; Interest Inventory; Career Exploration; Professional Growth; Personalized Recommendations; Career Pathways; Life Coaching; Decision-Making Support; AI based support